Cold plasma-Metal Organic Framework (MOF)-177 breathable system for atmospheric remediation. Issue 51 (September 2021) - Gorky, Fnu; Nambo, Apolo; Carreon, Maria L.
Graphical abstract: Plasma catalytic oxidation of Captured Methane & Carbon Dioxide on MOF-177 for synthesis of Methanol. Highlights: MOF-177 is presented as an efficient adsorbent of greenhouse gases such as methane and carbon dioxide. Non-thermal plasma pulses allow instant control over the desorption of greenhouse gases adsorbed on MOF-177. MOF-177 is employed as a dual function material, for adsorption of greenhouse gases and their conversion to methanol. Abstract: The direct capture of CO2 and CH4 from the atmosphere to stabilize the concentrations in the air to control global warming is accelerating. There are continued efforts to develop and optimize different technologies for capture and sequestration of these greenhouse gases from industrial emission sites. In this work we employed MOF-177 as an efficient CO2 and CH4 adsorbent at standard temperature and pressure conditions. We demonstrated the possibility of desorbing the gases under study when employing gentle plasma pulses of He. Moreover, we performed the synthesis of methanol from CH4 using O2 and CO2 as oxidants respectively in the presence of MOF-177. We observed the highest conversion for the CH4 + O2 system when employing the MOF-177 at (5:1) (CH4 : O2 ) flow ratio of 23.5 % and methanol selectivity of 17.65 %. While the best performance for the CH4 + CO2 system at the same conditions i.e., (5:1) (CH4 : O2 ) flow ratio was 18.4 % for the methane conversion and 11.68 % for the selectivity towards methanol. We expect this preliminary understanding of the adsorption-reaction system under non-thermal plasma environment can lead to future atmospheric remediation technologies.